Martin Luther’s Role in Mending the Conditions of Europe Jews - Al Sabateen, Rajeh (DIRASAT: SHARI’A AND LAW SCIENCES, 2016)
This research which consists of four sections deals with the great role played by the German Monk "Martin Luther" in changing the conditions of Jews in Europe in Middle Ages, and limiting, persecuting them and their suffering. This monk was the first to proclaim that "Jesus was born a Jew" therefore, the Jews had done the Christians a great favor that should not be ignored by any Christian. This monk also proclaimed that the New Testament completes the Old Testament, and to understand the New Testament, we should first study and understand the Old Testament. In his last days, Martin Luther faced troubles with the Jews as a result of his latest books. But he remains a man who had the upper hand on them and did them a great favor at least, till the present day.